Combustion Characteristics of Diesel-Hydrogen Dual Fuel Engine at Low Load - W. B., Santoso; R. A., Bakar; Nur, A. (Elsevier Ltd, 2013)
In the present study, hydrogen utilization as diesel engine fuel at low load operation was investigated. Hydrogen cannot be used directly in a diesel engine due to its auto ignition temperature higher than that of diesel fuel. One alternative method is to use hydrogen in enrichment or induction. To investigate the combustion characteristics of this dual fuel engine, a single cylinder diesel research engine was converted to utilize hydrogen as fuel. Hydrogen was introduced to the intake manifold using a mixer before entering the combustion chamber. The engine was run at a constant speed of 2000 rpm and 10 Nm load. Hydrogen was introduced at the flow rate of 21.4, 36.2, and 49.6 liter/minute. Specific energy consumption, indicated efficiency, and cylinder pressure were investigated. At this low load, the hydrogen enrichment reduced the cylinder peak pressure and the engine efficiency. The reaction progress variable and combustion rate of reaction were slower as shown by the CFD calculation.